2021
DOI: 10.3390/ijms22094360
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Chloroxylenol by Cunninghamella elegans IM 1785/21GP and Trametes versicolor IM 373: Insight into Ecotoxicity and Metabolic Pathways

Abstract: Chloroxylenol (PCMX) is applied as a preservative and disinfectant in personal care products, currently recommended for use to inactivate the SARS-CoV-2 virus. Its intensive application leads to the release of PCMX into the environment, which can have a harmful impact on aquatic and soil biotas. The aim of this study was to assess the mechanism of chloroxylenol biodegradation by the fungal strains Cunninghamella elegans IM 1785/21GP and Trametes versicolor IM 373, and investigate the ecotoxicity of emerging by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The proposed mechanism of antimicrobial action of chloroxylenol also involves the inactivation of enzymes, the denaturation of essential proteins and alteration of the cell-membrane permeability, leading to uncoupled mitochondrial oxidative phosphorylation. The application of chloroxylenol as a bioactive agent in soaps, as a preservative and disinfectant and in liquid and anti-septic surgical scrubs has been reported, 47 but no literature are available on the application of chloroxylenol on textiles for its bioactive properties. The development of a chloroxylenol-based non-leaching bioactive reactive dye for bioactive textiles is both a sustainable and novel approach that shows strong antimicrobial potential, as revealed for the synthesized dye in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism of antimicrobial action of chloroxylenol also involves the inactivation of enzymes, the denaturation of essential proteins and alteration of the cell-membrane permeability, leading to uncoupled mitochondrial oxidative phosphorylation. The application of chloroxylenol as a bioactive agent in soaps, as a preservative and disinfectant and in liquid and anti-septic surgical scrubs has been reported, 47 but no literature are available on the application of chloroxylenol on textiles for its bioactive properties. The development of a chloroxylenol-based non-leaching bioactive reactive dye for bioactive textiles is both a sustainable and novel approach that shows strong antimicrobial potential, as revealed for the synthesized dye in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6c) (Fan et al 2019). preservative and anti-septic surgical scrubs has been reported (Nowak et al 2021) but no literature is available on the application of chloroxylenol on textiles for bioactive properties.…”
Section: H 1 -Nmr and C 13 -Nmr Analysismentioning
confidence: 99%
“…Several investigations were conducted to determine cytochrome P450 involvement in the decolorization of dyes 53 or elimination of xenobiotics. For example, our research team previously found involvement in the degradation of tributyltin (TBT) by Cunninghamella elegans 54 , 2,4-dichlorophenoxyacetic acid (2,4-D) by Umbelopsis isabellina 55 , 4- n -nonylphenol (4- n- NP) by Metarhizium robertsii 56 or chloroxylenol (PCMX) by C. elegans IM1785/21GP 57 . The involvement of cytochrome P450 monooxygenases of the N. pironii strain in o -tolidine biodegradation was verified using the competitive inhibitor 1-aminobenzotriazole (ABT).…”
Section: Resultsmentioning
confidence: 99%
“…The increased ROS patterns measured in B. koreanus in response to these two disinfectants also differed. PCMX is widely used because it has low toxicity to humans and is biodegradable ( Nowak et al, 2021 ). However, in aquatic environments, PCMX is classified as a moderately toxic chemical based on its low LC values (7.7 mg L −1 for D. magna LC 50 -96 h) for invertebrates, unlike in vertebrates such as birds and fish (Table S7) ( EPA, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…When a novel coronavirus (SARS-CoV-2) caused the COVID-19 outbreak, disinfection of surfaces was recommended as one of the most effective ways to prevent infection ( Ijad et al, 2021 ; Nowak et al, 2021 ). However, the chemicals recommended for hard-surface disinfectants and hand sanitizers for COVID-19 are classified as biocide and could have adverse effects, especially when high demand for them causes wide spread release ( Merchel Piovesan Pereira and Tagkopoulos, 2019 ; Dev Kumar et al, 2020 ; Tan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%